Dodecanol, metabolite of entomopathogenic fungus Conidiobolus coronatus, affects fatty acid composition and cellular immunity of Galleria mellonella and Calliphora vicina - Michalina Kazek; Agata Kaczmarek; Anna Katarzyna Wrońska; Mieczysława Irena Boguś (Scientific Reports, 2021)
Abstract One group of promising pest control agents are the entomopathogenic fungi; one such example is Conidiobolus coronatus, which produces a range of metabolites. Our present findings reveal for the first time that C. coronatus also produces dodecanol, a compound widely used to make surfactants and pharmaceuticals, and enhance flavors in food. The main aim of the study was to determine the influence of dodecanol on insect defense systems, i.e. cuticular lipid composition and the condition of insect immunocompetent cells; hence, its effect was examined in detail on two species differing in susceptibility to fungal infection: Galleria mellonella and Calliphora vicina. Dodecanol treatment elicited significant quantitative and qualitative differences in cuticular free fatty acid (FFA) profiles between the species, based on gas chromatography analysis with mass spectrometry (GC/MS), and had a negative effect on G. mellonella and C. vicina hemocytes and a Sf9 cell line in vitro: after 48 h, almost all the cells were completely disintegrated. The metabolite had a negative effect on the insect defense system, suggesting that it could play an important role during C. coronatus infection. Its high insecticidal activity and lack of toxicity towards vertebrates suggest it could be an effective insecticide.